Implementasi Kebijakan Pendidikan Lingkungan Hidup Di Sekolah Islam Terpadu Dalam Kajian Literatur - Dedik Dwi Prihatmoko (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2020)
Every country has different environmental problems that have an impact on the variety of policies and implementation of environmental education. The development of environmental education is dynamic and attracts attention so that it is always discussed in order to find solutions. Integrated Islamic Schools (SIT) in Indonesia also need to consider it as a major part of their education even though the leveled schools from elementary to secondary level have specificities in the implementation of Islamic character. The offer of literature on environmental education policies is described, although not in its entirety, it is selected in order to obtain an important strategy for its implementation in SIT education. The three policies have provided insight into how environmental education should be applied in SIT. The combination strategy with acculturation and habituation is expected to provide a buffering force for character education for all parties involved in integrated education from an integrated Islamic school.